2017
DOI: 10.5152/etd.2017.15070
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Cytogenetic Evaluations of Patients with Turner Syndrome: Are We Aware Enough?

Abstract: Objective: The objective of the present study was to describe the phenotypic features of Turner syndrome (TS) and to investigate the relationship between the genotype and the phenotype. Materials and Methods:We studied 26 female patients who were enrolled between 2006 and 2015. Physical features, clinical history, laboratory findings, and imaging test results were recorded. Chromosomal analysis was performed on peripheral blood lymphocyte cultures of the patients. Results:The mean age of the study population w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…12,20,21 Thus, early intervention should be done for orchidectomy. 22 In this study we observed 1 patient with marker chromosome 45,X(98%)/46,X mar(2%) with clinical profile of this patient showed short stature and no other dysmorphic features, compared to the previous study which reported severe phenotype manifestations in those type of Turner variants, 16 this could be due to the low percentage of marker X. Although, the conventional cytogenetic cannot detect the origin of marker chromosome, the molecular cytogenetic techniques, FISH, can accurately detect it.…”
Section: Discussionmentioning
confidence: 53%
See 4 more Smart Citations
“…12,20,21 Thus, early intervention should be done for orchidectomy. 22 In this study we observed 1 patient with marker chromosome 45,X(98%)/46,X mar(2%) with clinical profile of this patient showed short stature and no other dysmorphic features, compared to the previous study which reported severe phenotype manifestations in those type of Turner variants, 16 this could be due to the low percentage of marker X. Although, the conventional cytogenetic cannot detect the origin of marker chromosome, the molecular cytogenetic techniques, FISH, can accurately detect it.…”
Section: Discussionmentioning
confidence: 53%
“…Although, the conventional cytogenetic cannot detect the origin of marker chromosome, the molecular cytogenetic techniques, FISH, can accurately detect it. 16,17 In this study we observed a patient with translocation between chromosome 1 and X. Besides primary amenorrhea, patient also had short stature.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations